Investigation of Flowback Behavior for Multi-Fractured Horizontal Wells in Gulong Shale Oil Reservoir Based on Numerical Simulation - Shuxin Yu; Yucheng Wu; Xiaogang Cheng; Binhui Li; Langyu Niu; Rui Wang; Pin Jia; Linsong Cheng (Energies)
After hydraulic fracturing, hydraulic fractures and opened beddings are intertwined, which results in a complex fracture network in shale oil reservoirs. In addition, the migration of multi-phase fluids during fracturing and shut-in processes leads to complex flowback performance and brings difficulty to flowback strategies optimization. In this paper, taking the Daqing Gulong shale reservoir as an example, a numerical model, which considers oil–water–gas three-phase flow and the orthogonal fracture network, has been established for flowback period. The characteristics and influencing factors of flowback performance have been deeply studied, and the flowback modes of shale oil are reasonably optimized. Geological factors such as PTPG (pseudo-threshold pressure gradient), matrix permeability, and engineering factors such as opened bedding stress sensitivity, opened bedding permeability, and fracturing fluid distribution have obvious effects on the flowback performance, resulting in significant variations in production peaks, high production periods, and decline rates. Furthermore, three flowback modes distinguished by the BHP (bottom hole pressure) correspond to the three types of choke mode that have been optimized. This study reveals the main factors affecting the flowback performance. Meanwhile, the optimization method can be applied to optimize flowback strategies in Gulong and other similar shale reservoirs to obtain higher shale oil production.